Effect of dietary supplementation of prebiotic on growth performance, immune response and intestinal microbial load in broiler chickens - MEESAM, R; BISWAS, A; NAMIT, M; MANDAL, A B (The Indian Journal of Animal Sciences, 2019)
The experiment was conducted to study the effect of using prebiotic (mannan oligosachharide -MOS) in place of antibiotic growth promoter (AGP) on performance, immune response and intestinal microbial load in broiler chickens. Day-old broiler chicks (192) were randomly distributed into 20 groups each of 8 chicks (4 treatments Ã— 6 replicates). Four experimental diets T1, T2, T3 and T4 were formulated to contain no additive, bacitracin methylene di-salicylate (BMD) at 20 mg/kg diet, MOS at 0.1 and 0.2%, respectively. Body weight gain (g) was increased by the feeding of diets containing 0.2% levels of MOS, but feed intake (g), feed conversion ratio (FCR) and mortality (%) did not differ significantly. Antibody (28 d), titres were significantly higher after feeding 0.1 or 0.2% MOS and antibiotic (T2) supplemented group. During d 35, the response to intra-dermally injected phyto-hemagglutinin, an index of the in vivo cell-mediated immune response, was increased in the 0.2% MOS supplemented group. Significant reduction was observed in coliforms and total plate count in cecal (28 and 42 d) and excreta (42 d) in MOS (0.1 or 0.2%) or antibiotic (T2) supplemented groups. Lactobacillus count significantly increased in cecal (28 and 42 d) and excreta (42 d) in MOS @0.1 or 0.2% supplemented groups. Thus, it can be concluded that, 0.2% MOS with basal diet has a beneficial effect for growth performance, immune response and gut health status in broiler chickens, and MOS could be a good alternative to antibiotic growth promoter.